Association Between Inflation and Price of Assets in the crises Period - Ullah, Naqeeb (2025)
The study evaluated the association between inflation and Pakistan’s asset prices during the crisis. The country’s economic condition went through different crises, such as the Global Financial Crisis 2008-09 and COVID-19 from 2019-2020, which also created shifts in the monetary policy. The country’s inflation rate increased during the crisis, affecting asset prices. Therefore, considering the crisis periods, this study has been conducted to identify the relationship between inflation and asset prices. The study was conducted using a quantitative research design with secondary data. The data for inflation, stock price, exchange rate and gold prices were obtained through Trading Economics, OPF, and Investing.com. The data for the crisis period were considered using a dummy variable. The data was collected quarterly from 2012 to 2020. The time series data analysis was conducted using STATA software. Based on the results obtained from the ARDL test, the stock prices, exchange rate, and gold prices were significantly related to the inflation rate, considering the crisis interaction. Therefore, it was concluded that the inflation rate and prices of assets are significantly related, considering the economic crisis. Hence, policymakers should closely monitor inflation, especially during economic crises, to stabilise asset prices. Adaptive monetary policies and strong financial oversight can help manage the inflation’s impact on stocks, gold and exchange rates.